2017
DOI: 10.1080/17445647.2017.1354786
|View full text |Cite|
|
Sign up to set email alerts
|

Gaussian simulation of nitrate concentration distribution in the Zagreb aquifer

Abstract: Nitrates present one of the most common groundwater contaminants in the world and one of the five major groups of contaminants in the study area. Gaussian simulation (GS) algorithm was used for determining the spatial distribution of average nitrate concentrations from 2010 to 2015 on 95 sampling points. Results indicate two main focus areas of nitrate contamination, located on the left and right bank of the Sava River. Those areas generally extend according to groundwater flow, while areas near Sava River hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
13
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 22 publications
6
13
0
Order By: Relevance
“…The reason is seen in the appearance of statistically significant ascending trends in the area of well fields Petruševec, Sašnjak, and Žitnjak, all of which are located on the left bank of the Sava River. All results suggested that nitrate concentrations decrease over time in almost all areas, and this coincides with previous results [6,7]. In those areas where nitrate concentrations are increasing over time, concentrations are still much lower than 50 mg/L of NO 3 − , which is the maximum permissible concentration according to the Drinking Water Directive [41].…”
Section: Resultssupporting
confidence: 78%
See 4 more Smart Citations
“…The reason is seen in the appearance of statistically significant ascending trends in the area of well fields Petruševec, Sašnjak, and Žitnjak, all of which are located on the left bank of the Sava River. All results suggested that nitrate concentrations decrease over time in almost all areas, and this coincides with previous results [6,7]. In those areas where nitrate concentrations are increasing over time, concentrations are still much lower than 50 mg/L of NO 3 − , which is the maximum permissible concentration according to the Drinking Water Directive [41].…”
Section: Resultssupporting
confidence: 78%
“…Nitrate concentrations are higher in the upper part of the unsaturated zone, while concentrations generally decrease with depth [33]. This is consistent with lower nitrate concentrations observed in the groundwater of Zagreb aquifer [6,7]. Shallower Holocene aquifer varies in thickness from five to 40 m, while deeper aquifer extends up to 60 m [34].…”
Section: Research Areasupporting
confidence: 67%
See 3 more Smart Citations